2021
DOI: 10.35808/ersj/2026
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Electromobility in Poland: Consumer Attitude Assessment

Abstract: Purpose: The article presents selected research results concerning the Polish path of electromobility development. The subject of the research was to gain extensive knowledge about contemporary consumer attitudes. This goal was achieved by trying to identify the most important factors determining the choice of electric vehicles by the demand side in the Polish automotive market. Approach / Methodology / Design: CAWI techniques were used in the study. The study was conducted at the turn of 2020 and 2020. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…To this end, according to Directive 2009/28/EC [2], EU Member States should gradually increase the share of energy from their renewable sources, both in total energy consumption and in the transport sector. The problem related to CO 2 emissions in transport has been widely described in publications [25][26][27][28][29][30][31][32][33][34][35][36]. In Poland, despite production of energy from renewable sources is growing every year, the country's main source is still conventional energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, according to Directive 2009/28/EC [2], EU Member States should gradually increase the share of energy from their renewable sources, both in total energy consumption and in the transport sector. The problem related to CO 2 emissions in transport has been widely described in publications [25][26][27][28][29][30][31][32][33][34][35][36]. In Poland, despite production of energy from renewable sources is growing every year, the country's main source is still conventional energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of charging hotspots in advance will help power grid operators check whether grid reinforcement is required to support the increasing EV adoption. The planning model adopted in this case study performed better than the model reported in [114][115][116][117]. The third case study predicted the charging demand in Helsinki using a hybrid Bayesian network and RF-based methodology.…”
Section: Discussionmentioning
confidence: 92%
“…Research on electromobility development in Poland indicates that Polish consumers still perceive electric cars as expensive. According to Lewicki et al [50], this implies the need for more active government action to support the demand side.…”
Section: Background and Literature Review 21 Previous Research On Ev ...mentioning
confidence: 99%